2002
DOI: 10.1002/gcc.10154
|View full text |Cite
|
Sign up to set email alerts
|

Genomic anatomy of the specific reciprocal translocation t(15;17) in acute promyelocytic leukemia

Abstract: The genomic breakpoints in the t(15;17)(q22;q21), associated with acute promyelocytic leukemia (APL), are known to occur within three different PML breakpoint cluster regions (bcr) on chromosome 15 and within RARA intron 2 on chromosome 17; however, the precise mechanism by which this translocation arises is unclear. To clarify this mechanism, we (i). assembled the sequence of RARA intron 2, (ii). amplified and sequenced the genomic PML-RARA junction sequences from 37 APL patients, and (iii). amplified and seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 55 publications
2
49
1
Order By: Relevance
“…It should be noted that the size of the PCR products varies in bcr2-positive cases, because of the variable breakpoint positions in exon 6 of the PML gene and inclusion of a variable number of RARA intron 2-derived nucleotides in the FG transcript. 156 Chimeric PML-RARA and RARA-PML transcripts are formed as a consequence of the reciprocal translocation between the PML and RARA loci. However, the observation that RARA-PML FG transcripts are present in most but not all APL cases, has favored the use of PML-RARA FG transcripts as PCR target for detection of APL cells at diagnosis and during monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the size of the PCR products varies in bcr2-positive cases, because of the variable breakpoint positions in exon 6 of the PML gene and inclusion of a variable number of RARA intron 2-derived nucleotides in the FG transcript. 156 Chimeric PML-RARA and RARA-PML transcripts are formed as a consequence of the reciprocal translocation between the PML and RARA loci. However, the observation that RARA-PML FG transcripts are present in most but not all APL cases, has favored the use of PML-RARA FG transcripts as PCR target for detection of APL cells at diagnosis and during monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of genomic breakpoints in patients with APL has revealed a complex pattern with microhomologies, deletions and inversions suggesting that the t(15;17) is likely to arise as a result of double-strand DNA breakage followed by nonhomologous end-joining. 16,17 However, an important issue that remains to be resolved is the nature of the hematopoietic progenitor that is the normal target of the PML-RARa fusion in this disease. In this review, we consider the pertinent experimental evidence to date, particularly with respect to different neoplastic conditions and its implications for the origin of APL.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis of myeloid translocation breakpoints has revealed that the majority probably result from NHEJ following DNA breakage, 4,33,38,39 however, the reason why some fusions are seen very frequently compared with other known or potential fusions is still unclear. By contrast, the mechanisms giving rise to many chromosomal translocations in lymphoid malignancies are believed to be the result of illegitimate lymphoid-specific recombination mechanisms, such as V(D)J 16,34,40,41 or class switch recombination.…”
Section: Discussionmentioning
confidence: 99%
“…3 Analysis to date has indicated that translocations in leukemia result from non-homologous end joining (NHEJ) following two double stranded DNA breaks; homologous recombination does not have a significant role. 4,5 The paradigm for translocations in leukemia is the Philadelphia (Ph) chromosome, the smaller derivative of the t(9;22). 6 The resultant BCR-ABL fusion gene is the defining marker of chronic myeloid leukemia (CML).…”
Section: Introductionmentioning
confidence: 99%